1992
DOI: 10.1111/j.1467-9507.1992.tb00115.x
|View full text |Cite
|
Sign up to set email alerts
|

Getting Along or Getting Your Own Way: The Development of Young Children's Use of Argument in Conflicts with Mother and Sibling

Abstract: The development of children's use of argument in conflicts with their mother and sibling during their fourth vear, a period of marked changes in their understanding of others, was studied in 49 children observed at home with their mothers and siblings at 33 and 47 months. Children's use of reasoned argument in conflict increased: however, the proportion used for conciliation and compromise decreased, and children used justifications increasingly to support their own position. Mothers, hut not siblings, changed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
48
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 15 publications
4
48
0
Order By: Relevance
“…In another study it was found that the large majority of 9--year--olds' utterances supported their own point of view (Pontecorvo & Girardet, 1993). It is important to stress that this early emerging confirmation bias does not entail a lack of ability to attack arguments-when they are the arguments of the other party in the conflict (Howe, Rinaldi, & Jennings, 2002;Tesla & Dunn, 1992). One could argue, however, that observing such biases in situations of conflict is only to be expected.…”
Section: The Confirmation Biasmentioning
confidence: 95%
“…In another study it was found that the large majority of 9--year--olds' utterances supported their own point of view (Pontecorvo & Girardet, 1993). It is important to stress that this early emerging confirmation bias does not entail a lack of ability to attack arguments-when they are the arguments of the other party in the conflict (Howe, Rinaldi, & Jennings, 2002;Tesla & Dunn, 1992). One could argue, however, that observing such biases in situations of conflict is only to be expected.…”
Section: The Confirmation Biasmentioning
confidence: 95%
“…This finding is at least partially consistent with previous research that has identified children's development stage, and hence their cognitive capacity, as important in explaining sibling behaviour problems (e.g., Dunn et al, 1996;Tesla & Dunn, 1992). However, parents were less likely to see themselves as the cause of conflict, with differential parental treatment and over-interference from parents as among the least likely causes.…”
Section: Discussionsupporting
confidence: 89%
“…Whether it's the age gap between siblings (Dunn et al, 1994;Howe & Recchia, 2006;Pepler, Abramovitch, & Corter, 1981), sibling birth order (Brody, Stoneman, MacKinnon, & MacKinnon, 1985;Howe & Recchia, 2006), developmental stage (Dunn, Creps, & Brown, 1996;Dunn & Munn, 1985;Tesla & Dunn, 1992), parental marital status and conflict (Harrist et al, 2014;Iturralde, Margolin, & Shapiro, 2013), parent gender , peer influences (Bassett Greer, Campione-Barr, Debrown, & Maupin, 2014), or parental favouritism (Richmond, Stocker, & Rienks, 2005), the factors influencing sibling relationships are diverse and plentiful. Interestingly, however, although previous research has identified that parents consider their children's sibling relationships among the most significant issues they face (Ralph et al, 2003), few, if any, studies directly have asked parents what they believe are the underlying causes of their children's sibling relationship problems.…”
Section: The Significance Of Sibling Conflictmentioning
confidence: 99%
“…A previous study in Cambridge, England, documented how during the second and third year, children increasingly used their growing understanding of excuses and social rules to shift blame and responsibility for transgressions to their siblings and to get them into trouble (Dunn, 1988). And in the Pennsylvanian study the analyses of conflict when the children were 33 months old showed that the purpose for which a reasoned argument is used needs to be considered separately from the issue of whether a child provides some justification or argument for her position, or simply insists on her own way without justification (Slomkowski & Dunn, 1992;Tesla & Dunn, 1992). The evidence showed that argument can be employed in a non-conciliatory way, as in the first example cited above, or in a conciliatory fashion, as in the secund.…”
mentioning
confidence: 97%